2014
DOI: 10.5539/apr.v6n4p16
|View full text |Cite
|
Sign up to set email alerts
|

Textural, Structural and Electrical Characterizations of EMIMAc Silica Ionogels and Their Corresponding Aerogels

Abstract: Silica ionogels were synthesized from tetramethoxysilane (T MOS ),methyltrimethoxysilane (MT MS ) and 1-ethyl-2-methylimidazolium Acetate (EMI MAc: Ionic Liquid) in different proportions .The textural characterizations showed an effect of these concentrations on the corresponding aerogels: pore size distributions and effective surfaces. The structure of the aerogels was measured with a SAXS (Small-Angle XRay Scattering) apparatus and was typical of acid catalyzed aerogels. Conductivity voltage measurements, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
1
2
0
2
Order By: Relevance
“…the hydrolysis and condensation processes, counterbalancing the fast gelation tendency at high temperatures (to some extent). We rationalise that the presence of stable ≡Si-CH 3 groups in the silica monolith partially offsets the mechanical stress and thus the overall brittleness of the ionogels [19]. Fig.…”
Section: Resultssupporting
confidence: 68%
“…the hydrolysis and condensation processes, counterbalancing the fast gelation tendency at high temperatures (to some extent). We rationalise that the presence of stable ≡Si-CH 3 groups in the silica monolith partially offsets the mechanical stress and thus the overall brittleness of the ionogels [19]. Fig.…”
Section: Resultssupporting
confidence: 68%
“…However, extensive shrinkage of these ionogels over time (Figure 8e and f ) can result in the loss of electrode-ionogel contact and jeopardize the lifetime of the resultant EDLC. Mixing different alkoxysilanes together is often a way to improve the mechanical properties of the resultant ionogel 12,14 . However, attention must be paid to the compatibility of the precursors, as poor choice can result in heterogeneity in the gel (the more reactive precursor forms silica networks f aster).…”
mentioning
confidence: 99%
“…By removing MTMS from the formulation the gelation period dropped to 1 hour. It has also been shown that gel scaffolds containing higher molar ratio of MTMS to TMOS, possess higher BET surface area [108]. This shows that the slight variations in the formulation can induce significant changes in the structure of the gel network.…”
Section: Influence Of Formulation On Ionogelsmentioning
confidence: 96%